Ultrasound evaluation of gallbladder wall thickness for predicting severe dengue: a systematic review and meta-analysis - Amirhossein Shahsavand Davoudi; Hamid Harandi; Reza Samiee; Shayan Forghani; Keyhan Mohammadi; Maryam Shafaati (The Ultrasound Journal)
Abstract Background The prevalence of dengue fever (DF), a mosquito-borne viral disease, is rising worldwide. Its severe manifestations like thrombocytopenia and plasma leakage are associated with increased mortality. Ultrasound-detected gallbladder wall thickening (GBWT) has been suggested as a potential indicator of the severity of the disease. Aims This systematic review and meta-analysis evaluated the predictive value of GBWT in identifying patients at risk for severe dengue. Methods Following the PRISMA 2020 guidelines, we conducted a systematic search of Web of Science, PubMed, Embase, and Scopus. Among the inclusion criteria were original studies that assessed GBWT across various dengue severity categories. Then, we performed a meta-analysis using a random effects model and subgroup analyses based on severity criteria to determine the relationship between GBWT and severe dengue. Results For the meta-analysis, 19 studies qualified for the inclusion criteria. There was a significant association between GBWT and severe dengue, according to the odds ratio (OR) of 2.35 (95% CI 1.88–2.82, p < 0.001). The subgroup analysis revealed consistent results for thrombocytopenia (OR: 2.65) and plasma leakage (OR: 2.26), among other severity criteria. Conclusions A reliable ultrasound indicator, GBWT can help identify patients at risk for severe dengue early on, improving clinical decision-making and patient outcomes. However, the possibility of differential diagnosis requires cautious interpretation.